Proceedings of the Seventh COnference on Emerging Networking EXperiments and Technologies 2011
DOI: 10.1145/2079296.2079322
|View full text |Cite
|
Sign up to set email alerts
|

Assessing IPv6 through web access a measurement study and its findings

Abstract: Transitioning an infrastructure the size of the Internet is no small feat. We are in the midst of such a transition, i.e., from IPv4 to IPv6. IPv6 was standardized 15 years ago, but until recently there were few incentives to adopt it. The allocation of the last large block of IPv4 addresses changed that, and migrating to an IPv6 Internet has become more urgent. This migration is, however, still rife with uncertainties and challenges. The goal of this paper is to provide insight into this transition, and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
3
39
0
Order By: Relevance
“…Zhou et al [16] found that IPv6 paths have a higher delay and loss than their IPv4 counterparts, mainly due to its poor performance in IPv6-in-IPv4 tunnels. Nikkhah et al [17] and Dhamdhere et al [20] found that IPv6 delay is similar to IPv4 performance when the ASlevel paths are identical. Czyz et al [21] concluded that IPv6 RTT is getting better according to a long-term observation.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhou et al [16] found that IPv6 paths have a higher delay and loss than their IPv4 counterparts, mainly due to its poor performance in IPv6-in-IPv4 tunnels. Nikkhah et al [17] and Dhamdhere et al [20] found that IPv6 delay is similar to IPv4 performance when the ASlevel paths are identical. Czyz et al [21] concluded that IPv6 RTT is getting better according to a long-term observation.…”
Section: Related Workmentioning
confidence: 98%
“…Investigating the performance of IPv6 network is the basis of guaranteeing the network with a good performance. Therefore, many studies have been performed to analyze IPv6 network performance, as well as figure out the differences between IPv4 and IPv6 [13][14][15][16][17]. However, our understanding of IPv6 network cannot catch up with the speed of its development.…”
Section: Introductionmentioning
confidence: 99%
“…Kuehne [8] surveyed the IPv6 deployment by querying web and email servers of the top domains from Alexa for DNS AAAA records. Nikkah et al [36] compared the performance of IPv4 and IPv6 based on accessing a larger number of IPv6-capable web servers. CAIDA [37] visualised the IPv6 Internet topology based on routing information and active probing.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, a 2007 study [50] showed that IPv6 forwarding plane lagging behind its IPv4 counterpart, with routers/switches the primary culprits. Those early stability problems are, however, now over and a study we conducted in 2011 [36] showed that the IPv6 and IPv4 forwarding planes now perform similarly. [49].…”
Section: ) Itdsmentioning
confidence: 99%